The effect of hydrogen addition on methane-air flame in a stratified swirl burner. (15th February 2023) - Rahimi, Sajjad; Mazaheri, Kiumars; Alipoor, Alireza; Mohammadpour, Amirreza
Abstract: This numerical study has focused on assessing the influence of adding 20% and 40% hydrogen (on the volume of fuel basis) in different slots of a turbulent methane-air flame. The injection configurations are as follows: in the (i) inner slot, (ii) outer slot, (iii) and both slots. RANS numerical results has been obtained using OpenFOAM code. The impact of enrichment configuration and level on various flow fields have been investigated in the stratified and premixed cases. The results showed that adding hydrogen in the outer slot does not change the flow characteristics significantly, and adding H2 in both slots showed a slight difference compared to adding hydrogen in the inner slot. Hydrogen addition in the inner slot and both slots increased the combustion intensity near the burner exit and resulted in a robust flame attachment which is mainly the result of the enhancement of reaction rates of O H + H 2 = H + H 2 O and O H + C H 4 = C H 3 + H 2 O in the premixed case. In the stratified case, in addition to the pathways mentioned above, the reaction rate of H + O 2 = O + O H also enhanced, which resulted in better flame attachment. Regarding pollutant emissions, H2 addition, decreased CO and increased NOx emission in all configurations of the premixed and stratified cases. Highlights: Hydrogen-enriched premixed and stratified flames has been studied numerically. Different H2 addition configurations were examined in a dual inlet burner. Higher reactivity of H2 enhances flame attachment, especially in the stratified case. Hydrogen blending with methane increases the rate of CH4 consuming reactions. H2 addition increases NOx, and reduces CO in all configurations of both cases.